Modeling decision for artificial intelligence 8th International Conference, MDAI 2011, Changsha, Hunan, China, July 28-30, 2011, Proceedings - Torra, Vicenç; Narakawa, Yasuo; Yin, Jianping; Long, Jun (Lecture Notes in Computer Science, 2011)
This book constitutes the proceedings of the 8th International Conference on Modeling Decisions for Artificial Intelligence, MDAI 2011, held in Changsha, China, in July 2011. The 25 papers presented were carefully reviewed and selected from 43 submissions. The volume also contains extended abstracts of the three invited papers. The topics covered are aggregation operators and decision making; clustering and similarity; computational intelligence; and data privacy.